Theory of Power In Supreme Court Decision Nomor 23 P/Hum/2024 - Permana, Ajeng; Utami, Tanti; Aulia, Salsabila; Garnita, Camiliya; Mawardi, Muhamad (Journal Customary Law, 2025)
The Supreme Court Decision No. 23P/HUM/2024 on the minimum age limit for regional head candidates has come under scrutiny due to its impact on legal principles, politics, and public trust. This research discusses the application of power theory in the decision, highlighting the role of the Supreme Court as a guardian of the rule of law and the principle of checks and balances. Using a qualitative method, this research analyses the legal process, impact, and public response to the ruling, which stipulates that a candidate's age is calculated from the time of inauguration, not determination. This decision has raised pros and cons: on the one hand, it is considered inclusive of the younger generation, but on the other hand, it has triggered accusations of political manipulation. The survey showed that the majority of the public understood the importance of the Supreme Court's involvement in maintaining justice, despite concerns about the transparency of the process. The conclusion underscores the importance of caution in the formation of regulations to reflect legal integrity and maintain public trust.